2005
DOI: 10.1097/01.ccm.0000162559.74446.09
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic comparison between conventional mechanical ventilation and transtracheal open ventilation in acute traumatic quadriplegic patients*

Abstract: In acute quadriplegic patients receiving mechanical ventilation, TOV was as effective as EIV in providing ventilatory support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Furthermore, the patients who received transtracheal open ventilation spent significantly fewer days on mechanical ventilation and in the ICU than those who underwent conventional ventilation. Although several observational and physiologic studies have demonstrated the feasibility and the potential advantages of open ventilation (11)(12)(13)(14), this is, to our knowledge, the first randomized controlled trial showing the clinical benefits of delivering mechanical ventilation through an uncuffed tube, compared with the conventional approach based on the use of a cuffed tube.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, the patients who received transtracheal open ventilation spent significantly fewer days on mechanical ventilation and in the ICU than those who underwent conventional ventilation. Although several observational and physiologic studies have demonstrated the feasibility and the potential advantages of open ventilation (11)(12)(13)(14), this is, to our knowledge, the first randomized controlled trial showing the clinical benefits of delivering mechanical ventilation through an uncuffed tube, compared with the conventional approach based on the use of a cuffed tube.…”
Section: Discussionmentioning
confidence: 89%
“…Because of the high resistance of the small-bore tube and of the air leaks through the upper airway, the pressure distending the lung during transtracheal open ventilation is actually much less than the pressure applied to the airway opening (11)(12)(13)(14)(25)(26)(27). Uchyiama and colleagues found that a preset inspiratory pressure of 50 cm H 2 O resulted in an actual tracheal pressure of 4-5 cm H 2 O (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23][24][25][26][27] There was moderate evidence to support the use of an assist cough to improve cough efficacy by significantly increasing peak expiratory flow 21 and that the use of trans-tracheal open ventilation (mechanical ventilation through minitracheostomy) 22 was effective in maintaining gas exchange and respiratory mechanics for an initial 24 h period. There was also moderate evidence for the provision of respiratory muscle resistance training to improve maximum inspiratory pressure 24,25 and vital capacity.…”
Section: Results: Physiological Outcomesmentioning
confidence: 99%